2016
DOI: 10.1002/adfm.201504185
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Nanoparticle Facilitated Drug Delivery for Cancer Therapy with Targeted and Image‐Guided Approaches

Abstract: With rapid advances in nanomedicine, magnetic nanoparticles (MNPs) have emerged as a promising theranostic tool in biomedical applications, including diagnostic imaging, drug delivery and novel therapeutics. Significant preclinical and clinical research has explored their functionalization, targeted delivery, controllable drug release and image-guided capabilities. To further develop MNPs for theranostic applications and clinical translation in the future, we attempt to provide an overview of the recent advanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
154
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 254 publications
(155 citation statements)
references
References 168 publications
(192 reference statements)
1
154
0
Order By: Relevance
“…Results from a Phase II/III clinical trial in over 2000 patients for MRI detection of lymph future science group MNPs for precision oncology: theranostic magnetic IONPs for image-guided & targeted cancer therapy Review node metastasis showed that it is safe to administer 2.9 mg Fe/kg dose of magnetic SPIONs (30 nm size) in humans as SPIONs were taken up by the macrophages in the spleen, liver and lymph nodes [77,78]. In general, a clinical dose of IONPs in humans (0.56-3 mg Fe/kg) will be much less than the normal blood iron concentration (≈33 mg Fe/kg body weight) and total body iron (≈3500 mg) [14]. Thus, it is likely that magnetic IONP-based drug carriers have less safety concern than other nanomaterials for the translational development of new theranostic agents for image-guided and targeted cancer therapeutic approaches.…”
Section: Biodistribution Safety and Degradationmentioning
confidence: 99%
See 2 more Smart Citations
“…Results from a Phase II/III clinical trial in over 2000 patients for MRI detection of lymph future science group MNPs for precision oncology: theranostic magnetic IONPs for image-guided & targeted cancer therapy Review node metastasis showed that it is safe to administer 2.9 mg Fe/kg dose of magnetic SPIONs (30 nm size) in humans as SPIONs were taken up by the macrophages in the spleen, liver and lymph nodes [77,78]. In general, a clinical dose of IONPs in humans (0.56-3 mg Fe/kg) will be much less than the normal blood iron concentration (≈33 mg Fe/kg body weight) and total body iron (≈3500 mg) [14]. Thus, it is likely that magnetic IONP-based drug carriers have less safety concern than other nanomaterials for the translational development of new theranostic agents for image-guided and targeted cancer therapeutic approaches.…”
Section: Biodistribution Safety and Degradationmentioning
confidence: 99%
“…Finally, for clinical translation, it is important to use nanoparticles with strong and long-lasting imaging signals that can be detected by a clinical available imaging modality. At present, magnetic iron oxide nanoparticle (IONP) or superparamagnetic iron oxide nanoparticle (SPION) is one of the few nanoparticle platforms that fit the above criteria for the development of theranostic agents for clinical applications [14][15][16]. As increasing need of image-guided cancer therapy for designing personalized therapeutic protocols for cancer patients, advances in the translational development of IONPs should have significant impact on the clinical management and prognosis of cancer patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, without changing the drug itself, there is a great incentive to develop alternative, rapid and more effective chemotherapeutic approaches to direct the drug to its target [3]. Consequently, different Dox formulations and modifications that allow it to evade membrane transporters have been the subject of many new formulations, many of them are nanobased [4][5][6][7][8]. Particularly, special attention have been devoted to the significant role of magnetic iron oxide nanoparticles (MNPs) in enhancing intracellular drug uptake/anticancer drug accumulation inducing apoptotic cell death, and offering means to inhibit the cellular drug resistance, thus providing promising imaging/targeting potentials in leukemia therapy [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Upon interaction with the cancer-specific surface protein, the peptide-guided nanocarrier is internalized by the cancer cells. [10][11][12] However, a major…”
Section: Introductionmentioning
confidence: 99%